Describing language assessments for school-aged children: A Delphi study - Denman, D.; Kim, J.; Munro, N.; Speyer, R.; Cordier, Reinie (2018)
© 2018, The Speech Pathology Association of Australia Limited. Purpose: Given the barriers that inconsistent terminology poses for the Speech-Language Pathology (SLP) profession, this study aimed to develop an agreed-upon taxonomy with well-defined categories for describing language assessment practices for children. Method: A taxonomy with illustrative terms for describing assessments across four aspects (modality/domain, purpose, delivery and form) was developed with reference to contemporary literature. In a three round Delphi study, SLPs with expertise in child language were asked to indicate their level of agreement with the taxonomy and provide feedback. Participants were also asked to apply the taxonomy by categorising assessments presented in case studies. Result: A total of 55 participants completed round one, while 43 and 32 completed rounds two and three respectively. Agreed consensus with the taxonomy was achieved in both rounds one and two, with at least 88% of participants agreeing with each aspect and 100% agreeing with the overall structure. In round three, an agreement was reached on 7/10 components for one case study and 4/10 for the other. Conclusion: The development of this taxonomy represents a significant step towards providing detailed terminology for describing language assessments. Future research is needed to investigate implementation strategies to facilitate consistent application of the taxonomy by SLPs.